The Roles of Alpha-Momorcharin and Jasmonic Acid in Modulating the Response of Momordica charantia to Cucumber Mosaic Virus - Yang, Ting; Meng, Yao; Chen, Li-Juan; Lin, Hong-Hui; Xi, De-Hui (Frontiers in Microbiology, 2016)
Alpha-momorcharin (α-MMC) is a type-I ribosome inactivating protein (RIP) with a molecular weight of 29kDa that is found in Momordica charantia, and has been shown to be effective against a broad range of human viruses as well as having anti-tumor activities. However, the role of endogenous α-MMC under viral infection and the mechanism of the anti-viral activities of α-MMC in plants are still unknown. To study the effect of α-MMC on plant viral defense and how α-MMC increases plant resistance to virus, the M. charantia–cucumber mosaic virus (CMV) interaction system was investigated. The results showed that the α-MMC level was positively correlated with the resistance of M. charantia to CMV. α-MMC treatment could alleviate photosystem damage and enhance the ratio of glutathione/glutathione disulfide (GSH/GSSH) in M. charantia under CMV infection. The relationship of α-MMC and defense related phytohormones, and their roles in plant defense were further investigated. α-MMC treatment led to a significant increase of jasmonic acid (JA) and vice versa, while there was no obvious relevance between salicylic acid (SA) and α-MMC. In addition, reactive oxygen species (ROS) were induced in α-MMC-pretreated plants, in a similar way to the ROS burst in JA-pretreated plants. The production of ROS in both ibuprofen (JA inhibitor) and (α-MMC+ibuprofen)-pretreated plants was reduced markedly, leading to a greater susceptibility of M. charantia to CMV. Our results indicate that the anti-viral activities of α-MMC in M. charantia may be accomplished through the JA related signaling pathway.